Conductometric Studies of the Thermodynamics for Complexation of 1,1-Diethyl-3-(4-methoxybenzoyl)thiourea and Cobalt(II) Cation in Aqueous Binary Mixtures of Polar Organic Solvents - Suhud, K; Heng, LY; Rezayi, M; Al-Abbasi, AA; Hasbullah, SA; Ahmad, M; Kassim, MB (Springer/Plenum Publishers, 2024)
Indexed by WOS/ Scopus